1994
DOI: 10.1016/0741-5214(94)90014-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic carotid artery plaque structure and the risk of cerebral infarction on computed tomography

Abstract: Our results support the hypothesis that echolucent plaques are more frequently associated with symptoms and cerebral infarctions and provide further evidence that these plaques are unstable and tend to embolize. Studies on the natural history of asymptomatic carotid artery stenosis should investigate whether plaque characterization could identify a high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 18 publications
1
49
0
8
Order By: Relevance
“…[16] However, during the last decade an increasing number of reports have indicated that Bmode ultrasound images of the carotid plaque reveal features (echogenicity and structure) related to the presence of brain infarcts on computed tomography images [17] and to the risk of developing new neurological symptoms [2], [6], [20], [22], [25], [32], [38]. In other studies, where carotid endarterectomy was involved, the intensity of the reflected signals has been related directly to the amount of calcification and inversely to the amount of soft materials (lipids and hemorrhage) [8], [13], [31].…”
mentioning
confidence: 99%
“…[16] However, during the last decade an increasing number of reports have indicated that Bmode ultrasound images of the carotid plaque reveal features (echogenicity and structure) related to the presence of brain infarcts on computed tomography images [17] and to the risk of developing new neurological symptoms [2], [6], [20], [22], [25], [32], [38]. In other studies, where carotid endarterectomy was involved, the intensity of the reflected signals has been related directly to the amount of calcification and inversely to the amount of soft materials (lipids and hemorrhage) [8], [13], [31].…”
mentioning
confidence: 99%
“…Confirming these results, Bock et al 17 showed that echolucent plaques were associated with a 5.7% incidence of TIA and stroke, compared with only 2.4% for echogenic plaques (PϽ0.0001). In a cross-sectional study Geroulakos et al 38 found echolucent plaques to be associated with a higher incidence of brain infarcts on CT scans (PϽ0.02). As opposed to positive associations of plaque character to events found by the above-listed studies, Holdsworth et al 20 in a cross-sectional study of 4258 patients only found amaurosis fugax to be associated with echolucent and heterogeneous plaques, whereas the degree of stenosis overall seemed more predictive of events (PϽ0.00001).…”
mentioning
confidence: 99%
“…34,35 Large artery atherosclerosis, such as carotid plaque, is an established risk factor for cerebral infarction. 18,19,24 The role of orosomucoid in relation to carotid plaque burden is not known. However, in line with our study, a previous study reported elevated levels of orosomucoid in patients with carotid plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Orosomucoid has also been associated with carotid atherosclerosis, 16,17 which is a major stroke risk factor and a source of thromboembolism leading to stroke. 18,19 The purpose of this study was to examine the association between orosomucoid and carotid plaque in a populationbased cohort of men and women and to study whether elevated levels of orosomucoid modify the relationship between carotid plaque and stroke.…”
mentioning
confidence: 99%